Gestión interna de la empresa de Internet Jatnet S.A. en la ciudad de Babahoyo, periodo 2022. - Fuentes López, Lisbeth Dayana (2023)
The Internet services company Jatnet S.A located on Calle 10 de Agosto and Martín Icaza in front of the Hotel Capitol in the city of Babahoyo, the company provides Internet services and maintenance, in which you can see shortcomings in its internal management and administrative processes, for this reason, the objective is to carry out an analysis of the company to identify which procedures are affecting the problem that prevents the company from improving its management and its processes, in addition to the application of the methodology that was a questionnaire of questions directed towards the owner of the company and a survey carried out to the employees, with the result of the same the SWOT analysis was obtained, identifying their strengths, opportunities, weaknesses and threats of the company reaching the conclusion that the entity must improve a lot in internal control, train your staff, in addition to ensuring that your processes are followed correctly so that customer service improves.